Encelar(se), ¿una experiencia femenina? dilemas narcisos desde la perspectiva interseccional del género - Campos Guimarães, Maisa (2022)
Jealousy permeates affective relationships, becoming a subjective, relational and sociocultural phenomenon. In an intersectional reading of gender and race, the loving device is pointed out as central to the subjectivation of women. This qualitative research aimed to understand how women name, mean and deal with their own and / or love partners jealousy. Narrative interviews were conducted with 12 women, in hetero-affective relationships, with complaints about jealousy. By content analysis, the categories were organized between received jealousy (Being the “chosen one”; Normal vs. abnormal jealousy; Women´s self-responsibility and Men´s lack of responsibility) and sense (“Risk” of being abandoned, Jealous: from insecure to crazy?; Female rivalry exacerbated by racial and aesthetic dilemmas). Intersectional readings of emotionalities revealed how jealousy interpellates gendrized and racialized narcissistic dilemmas.